Extrinsic factors affecting water absorption in chilling of broiler chicken carcasses - Pinto, Marcos Franke [UNESP]; Nicolau, Juliana Pampana [UNESP]; Ponsano, Elisa Helena Giglio [UNESP]; Perri, Silvia Helena Venturolli [UNESP]; Garcia Neto, Manoel [UNESP] (My University, 2012)
Brazil occupies an outstanding position as a producer and exporter of chicken meat, and the maintenance and expansion of this position require a constant evolution, especially in variables which determine quality. An important quality parameter of poultry meat is the amount of water absorbed by the carcass during processing. In Brazil, carcasses chilling is done by immersion in chilled water. In this process, the carcass is rehydrated and the water lost during transport and initial operations is replaced. At this stage, some care is needed to prevent the absorption of water upper than the level allowed by Brazilian law. This project aimed to evaluate extrinsic factors that can influence the absorption of water by the chicken meat. For this, 144 Cobb chickens divided into 24 groups of six birds were used. At 42 days of age, one chicken of each group, with weight ranging up to 10% more or less from the average of the group, was slaughtered in an experimental pilot scale abattoir where slaughter procedures were conducted under strictly controlled conditions. The chilling procedure was performed following a completely randomized design with factorial arrangement 3x2, where the factors were: three temperatures in the first section of the chilling system (4, 10 and 16ºC) and two degrees of water hardness (hard and soft water), with six treatments and four replications. Brazilian law provides that the water temperature in the first section of the chiller must not be higher than 16ºC, and the length of the carcasses in this section shall not exceed 30 minutes. All carcasses remained in the first section of the chiller for 30 minutes and then were transferred to another tank with water at 4ºC, remaining there until reaching 7ºC. The carcasses were weighed before and after chilling, to evaluate the percentage of water absorbed. The water absorption was influenced by the initial temperature of the water in the chiller and by the water hardness. When initially immersed in water at 4ºC, carcasses water absorption averaged 2.70%, a significantly lower absorption than the values found for the carcasses that were initially immersed in water at 16ºC, 3.83% (p<0.05). The carcasses immersed in water at 10ºC had mean water absorption of 3.66%, not differing from the means observed in the other two treatments (p>0.05). In hard water, the average water absorption was 2.46% and, in soft water, 4.33% (p<0.05). In all treatments, the water absorption did not exceed the limit established by Brazilian legislation, which is a maximum of 8%. This information is important to control the absorption of water by carcasses in chicken meat processing, preventing consumers from being harmed.
Keywords: Quality control; Legal parameters; Immersion chilling; Water chilling; Poultry meat